2014
DOI: 10.1167/iovs.14-15553
|View full text |Cite
|
Sign up to set email alerts
|

Lutein and Zeaxanthin Supplementation and Association With Visual Function in Age-Related Macular Degeneration

Abstract: Lutein and zeaxanthin supplementation is a safe strategy for improving visual performance of AMD patients, which mainly showed in a dose-response relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(114 citation statements)
references
References 43 publications
3
98
2
5
Order By: Relevance
“…Consistent with data generated for visual function, higher macular pigment levels have been linked to improved critical licker fusion frequency [28][29][30][31], higher concentrations in the visual cortex [53], and improvements in electroretinography responses [32,33]. Bovier et al found moderate but statistically signiicant improvements in both MPOD and cognitive function with lutein and zeaxanthin supplementation of young, healthy individuals considered to be at peak cognitive eiciency [34].…”
Section: Neural Processingmentioning
confidence: 60%
See 1 more Smart Citation
“…Consistent with data generated for visual function, higher macular pigment levels have been linked to improved critical licker fusion frequency [28][29][30][31], higher concentrations in the visual cortex [53], and improvements in electroretinography responses [32,33]. Bovier et al found moderate but statistically signiicant improvements in both MPOD and cognitive function with lutein and zeaxanthin supplementation of young, healthy individuals considered to be at peak cognitive eiciency [34].…”
Section: Neural Processingmentioning
confidence: 60%
“…A stronger efect was noted for studies using higher doses of supplements. Interestingly, a linear association of MPOD and an increase in visual acuity was also measured [53].…”
Section: Age-related Macular Degeneration (Amd)mentioning
confidence: 83%
“…Namely, MP acts as a natural blue light filter that protects the eye from oxidative damage (Snodderly, 1995). It is also capable of enhancing contrast by adding luminance contrast information to an edge (Liu et al, 2015;Renzi and Hammond, 2010a). It has been related to visual performance and temporal vision (Renzi and Hammond, 2010b) and it is strongly related to improvements in glare disability and photo stress recovery (Stringham and Hammond, 2007).…”
Section: What Is the Function Of Carotenoids In The Eye?mentioning
confidence: 99%
“…Some epidemiological studies suggest that higher consumption of lutein and zeaxanthin is associated with lower risk of AMD (Whitehead et al, 2006). A recent meta-analysis including 8 randomized clinical trials involving 1176 AMD patients concluded that lutein and zeaxanthin supplementation was a safe strategy to improve visual performance of AMD patients (Liu et al, 2015). In fact, the study by Ma et al (2012) showed that electroretinogram responses increased after lutein supplementation alone or lutein + zeaxanthin supplementation for up to 6 or 12 months in early AMD patients.…”
Section: What Is the Function Of Carotenoids In The Eye?mentioning
confidence: 99%
“…Studies have shown that macular carotenoid supplementation provides myriad visual health benefits, including improved visual acuity, glare recovery, and contrast sensitivity function [11], along with increasing both neural processing speed and efficiency of visual signals [12]. Furthermore, macular carotenoid supplementation has been linked to improved cognitive function [13] and reduced cortisol levels.…”
Section: Introductionmentioning
confidence: 99%